Fixture congestion modulates post-match recovery kinetics in professional soccer players - Lundberg, T. R.; Weckström, L. (Research in Sports Medicine, 2017)
This study examined the influence of fixture congestion on physical performance and biochemical variables in professional male footballers. After 3 competitive matches within a week (3M cycle), 16 players underwent blood sampling and field testing 72 h after the last match. The same tests were performed after a regular 1 match-week cycle (1M cycle). The 1M vs. 3M change scores were compared between Congested (high match exposure) and non-selected Control players. The change score in muscle soreness was greater (effect size 1.0; CI 0.0-1.9) in the Congested players than Controls, indicating a possible negative effect of fixture congestion. There were no effects on sprint and jump performance. The change in plasma (P)-Urea was greater in Congested players than controls (effect size 1.3; CI 0.3-2.2). The effects on other blood variables were either non-existing/trivial, or unclear. Altogether, physical fitness and immune function were not compromised by match congestion, yet some indices of physiological stress and muscle damage were still evident.